2018
DOI: 10.1177/1753466618772750
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes in patients with chronic obstructive pulmonary disease initiating long-acting mono bronchodilator therapy

Abstract: Background:Randomized clinical trials have shown long-acting mono bronchodilator therapy to be efficacious in improving lung function and dyspnea, while reducing exacerbations; however, less is known regarding the effectiveness in routine clinical practice. This study examined treatment patterns, rescue medication use, healthcare resource utilization and costs, and exacerbations in patients with chronic obstructive pulmonary disease (COPD) who initiated long-acting mono bronchodilator therapy in real-world set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…A study based on insurance claims in the USA showed that patients who started long-term bronchodilator monotherapy showed high rates of treatment discontinuation or augmentation, as well as high rates of use of rescue therapy, and high treatment costs. 23 Another realworld study from the USA showed that patients starting a LAMA/LABA combination had higher adherence than patients starting an ICS/LABA combination. 24 Two studies from the United Kingdom revealed that the rate of prescribing according to the guidelines was low and that many patients were over-treated, and with poor adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study based on insurance claims in the USA showed that patients who started long-term bronchodilator monotherapy showed high rates of treatment discontinuation or augmentation, as well as high rates of use of rescue therapy, and high treatment costs. 23 Another realworld study from the USA showed that patients starting a LAMA/LABA combination had higher adherence than patients starting an ICS/LABA combination. 24 Two studies from the United Kingdom revealed that the rate of prescribing according to the guidelines was low and that many patients were over-treated, and with poor adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1 The recommended use of daily controller therapy for asthma and chronic obstructive pulmonary disease (COPD) has been associated with improved disease outcomes and decreased risk of respiratory exacerbations. [1][2][3] Increased adherence to daily medications is multifactorial and during the present pandemic may be driven by a patient's concern of his or her respiratory symptoms being associated or confused with COVID-19. Patients with well-managed symptoms are also less likely to seek acute respiratory care at health care facilities and emergency departments, which decreases the risk of incidental exposure to SARS-CoV-2 and allows health care providers to focus attention on patients with other critical needs.…”
mentioning
confidence: 99%
“…Our study also found that asthma control in children who closely followed daily medication regimens before the epidemic and reserved controller medication in advance was less affected by the epidemic. This finding reminds us that children with asthma should adhere to daily medication therapy at the ordinary times, especially during the COVID-19 outbreak, which can decrease the risk of respiratory exacerbations and improve asthma outcomes, [37][38][39] and that they should reserve medicines in advance according to doctors' prescriptions to cope with the challenges of COVID-19.…”
Section: Discussionmentioning
confidence: 77%